2009
DOI: 10.1097/mrr.0b013e32830d36b6
|View full text |Cite
|
Sign up to set email alerts
|

Needs of Indian parents having children with intellectual disability

Abstract: Disability in children gives rise to various needs in parents, which may vary according to the nature of disability and parental characteristics. Cross-cultural findings will help in understanding the process of meeting those needs, which ultimately help in designing appropriate interventions. The main objectives of the study were to compare the perceived needs of fathers and mothers having a child with intellectual disability, and to understand their cumulative needs with reference to the age, sex, and severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 9 publications
1
27
1
4
Order By: Relevance
“…In this context, it must be understood that parents' needs do not mean the personal needs of the parents, but the needs they experience for the child as is evident from several studies (Azar & Badr, 2010;Kermanshahi et al, 2008;Verma and Kishore, 2009). The needs of the parents appear to depend on personal resources of the parents, family variables and the characteristics of children, and more importantly the socio-cultural setting to which the families belong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it must be understood that parents' needs do not mean the personal needs of the parents, but the needs they experience for the child as is evident from several studies (Azar & Badr, 2010;Kermanshahi et al, 2008;Verma and Kishore, 2009). The needs of the parents appear to depend on personal resources of the parents, family variables and the characteristics of children, and more importantly the socio-cultural setting to which the families belong.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the prominent needs reported by the parents are related to personal care needs (Plant & Sanders, 2007), management of adaptive behaviors (McCarthy, Cuskelly, Van Kraayenoord & Cohen, 2006), medical (Neely-Barnes & Marcenko, 2004), technical, financial and social needs (Verma & Kishore, 2009). While these needs are common in the context of other disabilities and nondisabilities, the intensity of the above is usually very high and unique in intellectual disabilities (Peshawaria, 1995;Verma & Kishore, 2009;James & Ashwill, 2007& Peters & Jackson, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…While the needs of Indian parents have been fount not to vary with the severity of their child's ID,[29] in this study we observed, in both the CBR and clinical setting, that parents having children with mild and moderate ID were more concerned about their behavioral problems. This concern was likely one reason that these particular parents focused more on their child's behavioral management than parents having children with severe and profound ID.…”
Section: Discussionmentioning
confidence: 48%
“…In a study focusing on parents' needs [33 ], 30 couples, each having a child with intellectual disability, were assessed. The needs expressed by fathers and mothers differed significantly.…”
Section: Psychosocial Researchmentioning
confidence: 99%